ANALISIS ETIKA BISNIS ISLAM TERHADAP PERILAKU PENADAH IKAN EKSPOR DI KEC. MALLUSETASI KABUPATEN BARRU - Al Maidah Nur; Muhammad Kamal Zubair; Mukhtar Yunus (Institut Agama Islam Negeri Parepare, 2020)
Buying and selling activities is one of the activities of human life as an activity to meet needs. Islam does not justify any means of buying and selling, but also very much in need of ethics. Ethics is a set of moral principles that distinguish good from bad and normative, it plays the role of determining what must be done or not to be done by individuals or groups. In the ethics of buying and selling which is one of the most important things is the honesty of the two parties which is the culmination of the morality of faith and the most prominent characteristics of believers. Without honesty, religious life will not stand tall and world life will not go well.This study aims to determine the practice of buying and selling between fishermen and exporters of fish in the Mallusetasi District, Barru Regency. As well as an analysis of Islamic business ethics on the practice of buying and selling between fishermen and exporters of fish in the Mallusetasi District, Barru Regency. This type of research used in this thesis is a qualitative descriptive method, the data in this study were obtained from primary data and secondary data. Data collection techniques used were observation, interviews, and documentation. The data analysis technique is to use qualitative data analysis.The results of this study indicate that the buying and selling activities between fishermen and fishermen, the scales are regulated by the fishermen. Determination of the price determined by these collectors sometimes becomes a separate complaint by the fishermen. The number of complaints regarding the sale and purchase process carried out with the container. This is still a problem that often occurs. Moreover, when fishermen have no other place to sell their fish. In the practice of buying and selling examined by the author, there are still many problems. The location of the problem is the application of Islamic business ethics in export fish trading activities. In the buying and selling activities in the district. Mallusetasi almost all of its activities are not in accordance with the principles of Islamic business ethics